Au nanoparticle-loaded eggshell for electrochemical detection of nitrite. Issue 7 (20th January 2021) - Ding, Qi; Cao, Liping; Liu, Minghuan; Lin, Hetong; Yang, Da-Peng
Abstract : The schematic illustrates the preparation process of Au/CaCO3 nanocomposites. The bio-derived nanocomposites have successfully been applied for nitrite electrochemical detection. Abstract : Eggshell is an extremely large source of domestic waste and has a huge scientific research potential because of its unique porous hierarchical structure. By converting eggshell waste into valuable functional materials, it can be recycled in many fields. Herein, we envisioned an economical and environmentally friendly conversion method for synthesizing Au nanoparticle loaded eggshell nanocomposites (defined as Au/CaCO3 nanocomposites) for the detection of trace amounts of nitrite in oolong tea. Compared with bare electrodes, the prepared Au/CaCO3 nanocomposite-based electrodes have obvious electrochemical enhancement behavior. A wide linear response range of 0.01 to 1.00 mM and a relatively low detection limit of 11.55 nM have been obtained in this study. The "turning waste into treasure" transformation strategy not only provides a practical and low-cost method for comprehensive utilization of eggshells as valuable functional materials, but also provides a new approach for sensitive detection of pollutants.